miR-193b-365 microcluster downstream of Fezf2 coordinates neuron-subtype identity and dendritic morphology in cortical projection neurons - Asha Iyer; Lee O. Vaasjo; Verl B. Siththanandan; Rajan K C; Abbigail Thurmon; Mauren Akumuo; Victoria Lu; Chelsea Nnebe; Ramesh Nair; Maria J. Galazo; Suzanne Tharin (iScience)
Summary: Different neuron types develop characteristic axonal and dendritic arborizations that determine their inputs, outputs, and functions. Expression of fate-determinant transcription factors is essential for specification of their distinct identities. However, the mechanisms downstream of fate-determinant factors coordinating different aspects of neuron identity are not understood. Specifically, how distinct projection neurons develop appropriate dendritic arbors that determine their inputs is unknown. Here, we investigate this question in corticospinal and callosal projection neurons. We identified a mechanism linking the corticospinal/corticofugal identity gene Fezf2 with the regulation of dendritic development. We show that miR-193b∼365 microRNA cluster is regulated by Fezf2 and enriched in corticospinal neurons. miR-193b∼365 represses mitogen-activated protein kinase 8 (MAPK8) to regulate corticospinal dendritic development. miR-193b∼365 overexpression in callosal neurons abnormally reduces MAPK8 signal and dendritic complexity. Our findings show that regulation of MAPK8 via miR-193b∼365 cluster regulates dendritic development, providing a mechanism that coordinates projection neuron identity, specified by Fezf2, and neuron-specific dendritic morphology.